The sacred thread : Hinduism in its continuity and diversity - Brockington, J. L. (Edinburgh : Edinburgh University Press, 1996)
This classic introduction to Hinduism, now updated and including 14 illustrations of the Hindu deities, takes the Western reader through the concepts of the Hindu faith, from its Vedic origins to its present development.
Prehistory of Hinduism -- Impersonal trends -- Theistic trends -- Unorthodox movements -- The orthodox synthesis -- Sectarian developments -- Bhakti in the South -- Bhakti in the North -- Revival and reform -- Tradition triumphant.
Includes bibliographical references (pages 210-216) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Hinduism; Hinduism -- History; Hindouisme; Hindouisme -- Histoire; Hinduism; RELIGION -- Hinduism -- General; RELIGION / Hinduism / General; Hinduism; Hinduismus; Hindoeïsme.; Hinduism; Religion; Philosophy & Religion; Hinduism; History